The BIM Manager's Handbook, Part 3 : Focus on Technology. - Holzer, Dominik (Wiley, 2015)
EPart 3: Focus on Technology: How do you ensure your organisation gets the most out of the BIM technology available' Dedicated to the main technology-related aspects of a BIM Manager's role, this ePart explains how to establish and manage an organisation's BIM-related tool-ecology and how to use BIM in order to link from design to fabrication. What do BIM Managers need to do in order ensure their teams use the right tools for the various tasks in design, construction and beyond' How do they connect them and how do they keep up with updates in this rapidly changing environment. This ePart highlights the challenges BIM Managers need to overcome in software, hardware and network selection. It also brings into focus the opportunities BIM Managers face in the changing context of BIM in the Cloud. Extending beyond technical know-how, it also offers advice on how to create a successful interface between the BIM Manager and the IT specialist(s). Obook ISBN: 9781118987803; ePub ISBN: 9781118987773; ePDF ISBN:9781118987766; published August 2015.